Decision-making processes among potential dropouts in vocational education and training and adult learning - Vibe Aarkrog; Bjarne Wahlgren; Christian Hougaard Larsen; Kristina Mariager-Anderson; Susanne Gottlieb (International Journal for Research in Vocational Education and Training (IJRVET), 2018)
Context: Aiming at gaining knowledge about students' thoughts and actions in deciding to stay in or drop out of an educational programme, an empirical study was conducted on dropout among 18-24-year-old students in VET and basic general adult learning. Approach: In order to pursue this aim, the study combined two sets of data: weekly student surveys and interviews with these same students. While the surveys provide a weekly snapshot of the students' thoughts regarding the probability of them continuing in the programme, their satisfaction with the educational programme as a whole, the specific lessons they attend, and the atmosphere at the school, the interviews contribute with detailed descriptions of the students' thoughts on the same matters. Findings: Based on the students' answers over an eight-week period, it was possible to trace a graph illustrating changes in the students' attitudes. These graphs can be placed within four categories of development: the stable, the positive, the unstable, and the negative. The latter can furthermore be differentiated as reflecting a stable decline, a fluctuating decline, or a sudden decline. In the interviews, the aim was to elicit the individual students' thoughts and actions at the points when their graphs took a turn. Conclusions: The findings show that the students' thoughts and actions concern matters both inside and outside the school. Furthermore, seemingly trivial matters in the students' lives are shown to have a potentially decisive influence on the students' thoughts about staying in or dropping out of a programme. These findings confirm the importance of focusing on students' decision-making processes in research on dropout. However, further research is needed to increase understanding of processes leading to decisions to drop out of education, including the qualification of methods to capture these processes.
Keywords: 330; VET; Vocational Education and Training; Dropout; Decision-Making Process; Teetering; Young Adults; Adult Learning